Soilwater chemistry in a holm oak ( Quercus ilex) forest: inferences on biogeochemical processes for a montane-Mediterranean area (Journal of Hydrology, 1995)
Soil solution and free-flowing soilwater were sampled at various depths for 3 years in a plot of holm oak (Quercus ilex L.) in the Montseny mountains (NE Spain). The soil solution retained at -65M kPa in the mineral soil at depths of 20 and 40 cm had a different chemistry from that of throughflow under the humic layer (H-layer throughflow) and, to a lesser extent, from deep subsurface flow. The dominant mobile anion in the soil solution and the deep flow was SO:-, whereas in the H-layer, SOi- was overridden by alkalinity. H-Layer throughflow chemistry was extremely variable, in consequence of the large number of biogeochemical processes affecting it (e.g. rainfall chemistry, dry deposition, leaching from canopy and litter, decomposition), and of the quantity of water available for transport of solutes. The chemistry of the soil solution was more predictable, as it was governed mainly by nutrient uptake, cation exchange reactions and the seasonal wetting and drying cycles. The chemistry of the deep subsurface flow was often intermediate between that of the soil solution and that of the H-layer throughflow; this suggested a mixture of displaced pre-event soil solution and of H-layer throughflow circulating through preferential flow paths. With humid antecedent conditions, the chemistry of the deep subsurface flow approached that of the soil solution. The cation concentration relationships in the soil solution were strongly linear. In a homogeneous soil, cation exchange theory predicts this to be expected only for cations of the same charge, whereas cations of different charges should follow power relationships. Our results, however, are consistent with a theoretical approach involving cation exchange reactions in a highly heterogeneous environment. Indeed, our study illustrates the heterogeneous nature of the soils, as the power relationship has been obscured completely. Soilwater chemistries were markedly different from those of streamwater, particularly under dry conditions. During baseflow, the stream is fed by groundwater, and the soils are probably disconnected from the stream. During humid periods, the chemistry of the streamwater tends toward that of the deep subsurface flow. Chemical hydrograph separation indicates that, on average, stormflow water comprises an approximately one to one mixture of groundwater and deep subsurface flow.

Precipitation, throughfall, soil solution and streamwater chemistry in a holm-oak (Quercus ilex) forest (Journal of Hydrology, 1990)
Bulk precipitation, throughfall, soil solution at 20 and 40 cm depths, and stream water were monitored for 2–4 years in a holm-oak forest on schists in the Montseny Mountains (NE Spain). Bulk precipitation was mildly acidic, with Ca2+ and SO2−4 as dominant ions. Canopy interactions produced a throughfall less acidic than bulk precipitation and enriched in all other ions. Large amounts of K+ were leached from the canopy. Magnesium in net throughfall behaved similarly to K+, and it is concluded that leaching makes a major contribution to Mg2+ enrichment beneath the canopy. Judging from the moderate increase of Na+ and Ca2+ in throughfall, dry deposition rates for both marine and continental aerosols were low in the studied stand, probably because of its sheltered topographic position within a well-vegetated massif, coupled with moderate tree height and low canopy roughness. Soil solution in the mineral soil was less acidic than throughfall. In common with most temperate forests, SO2−4 was the dominant mobile anion in the soil water, being largely accompanied by Ca2+. Potassium and NO−3 were depleted within the soil water with respect to throughfall, probably owing to biological uptake and cation exchange, and incorporation of K+ into clay lattices. Subsurface flow dominated the hydrology of the small forested catchment studied. Stream water was basic and rich in bicarbonate. Its chemistry revealed fast rates of weathering of sodium- and magnesium-bearing silicates (mainly albite and chlorite, respectively). Soil respiration and silicate hydrolysis resulted in HCO−3 being the dominant mobile anion in stream water. Calcium to chloride ratios were similar in bulk precipitation and in stream water, indicating that Ca2+ release from weathering has been counteracted by plant uptake. Nutrient uptake by this aggrading forest strongly influences the solution dynamics of K+, NO3 and Ca2+. It is concluded that: (1) this forest does not currently receive acidic atmospheric deposition; (2) the neutralization capacity of the soil-bedrock system is quite high; (3) biotic regulation and silicate weathering are the major processes shaping the solution biogeochemistry in this Mediterranean forest ecosystem.